Measurement of the top pair production cross section in 8 TeV proton-proton collisions using kinematic information in the lepton + jets final state with ATLAS - Alconada Verzini, María Josefina (2015)
A measurement is presented of the tt¯ inclusive production cross section in pp collisions at a center-of-mass energy of √s = 8 TeV using data collected by the ATLAS detector at the CERN Large Hadron pffiffi Collider. The measurement was performed in the lepton + jets final state using a data set corresponding to an integrated luminosity of 20.3 fb-1. The cross section was obtained using a likelihood discriminant fit and b-jet identification was used to improve the signal-to-background ratio. The inclusive tt¯ production cross section was measured to be 260 ± 1 (stat)+22-23(stat) ± 8 (lumi) ± 4 (beam) pb assuming a top-quark mass of 172.5 GeV, in good agreement with the theoretical prediction of 253+13-15 pb. The tt¯→ (e, μ) + jets production cross section in the fiducial region determined by the detector acceptance is also reported.